Updated educational program: a new direction, a new look - Syzdykova, A.I. (Publ.KarSU, 2017)
This article examines the prerequisites for updating the content of secondary education in Kazakhstan and the priorities for updating the educational program. It also describes the changes in education, the substantive differences between the updated curricula, the three key components of effective learning, the advantages of cri- terial evaluation, the pedagogical approaches to learning in the context of renewing the content of education, and the modern methods of teaching and learning.
Жaңaртылғaн білім бeру бaғдaрлaмacы: жaңa бaғыт, жaңa көзқaрac
Oбнoвлeннaя oбрaзoвaтeльнaя прoгрaммa: нoвoe нaпрaвлeниe, нoвый взгляд
Keywords: update the content of secondary education; skill; training program; appraisal; pedagogical approaches; competence